POTENSI ANTIBAKTERI EKSTRAK ETANOL BATANG WOLE WOE ASAL HALMAHERAH TENGAH TERHADAP BAKTERI Pseudomonas aeruginosa dan Bacillus subtilis MENGGUNAKAN METODE DIFUSI AGAR - Fitriana Fitriana; Sitti Amirah; Safriani Rahman; Bayu Putra (Fakultas Farmasi UMI, 2022)
The wole woe plant empirically in the community in Central Halmaherah district is used to treat various diseases, such as breast anticancer, cysts, vaginal discharge, diabetes mellitus, wounds, dysentery, cholesterol, and uric acid, which is thought to have bioactive compounds, that is antibacterial compounds. Therefore, a study was conducted to determine the antibacterial potential of the ethanol extract of wole woe stems against Pseudomonas aeruginosa and Bacillus subtilis bacteria using the agar diffusion method. The results of the screening test showed activity at a concentration of 0.1% and the results of the minimum inhibitory concentration test (MIC) and the minimum killing concentration test (MBC) obtained 1.6% for Pseudomonas aeruginosa bacteria. For Bacillus subtilis bacteria, the MIC value is 0.2% and the MBC value is 3.2%. The statistical test results of the inhibition zone diameter data from the antibacterial activity test against Pseudomonas aeruginosa and Bacillus subtilis bacteria showed that there was a difference in the ability to inhibit bacterial growth between the positive control and the test concentration group of 2.5%, 5% and 10%. The results obtained from the ethanol extract of wole woe stems have potential as antibacterial.